2010
DOI: 10.1093/ecam/nen078
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Endogenous β‐Endorphin in the Plasma Glucose‐Lowering Action of Herbal Products Observed in Type 1‐Like Diabetic Rats

Abstract: Recently, there have been advances in the development of new substances effective in managing diabetic disorders. Opioid receptors couple multiple systems to result in various biological effects, although opioids are best known for analgesia. In the present review, we used our recent data to describe the advance in plasma glucose-lowering action of herbal products, especially the mediation of β-endorphin in glucose homeostasis of insulin-deficient diabetes. In type 1-like streptozotocin-induced diabetic rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 144 publications
0
28
0
Order By: Relevance
“…It has been indicated that opioids secreted from the adrenal gland can lower plasma glucose in STZ‐diabetic rats . Additionally, β‐endorphin is involved in the plasma glucose‐lowering action of herbal products . Therefore, we speculated that the action of diosmin in STZ‐diabetic rats is also associated with β‐endorphin secretion.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been indicated that opioids secreted from the adrenal gland can lower plasma glucose in STZ‐diabetic rats . Additionally, β‐endorphin is involved in the plasma glucose‐lowering action of herbal products . Therefore, we speculated that the action of diosmin in STZ‐diabetic rats is also associated with β‐endorphin secretion.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of β‐endorphin binding receptor is elevated in the skeletal muscle of type‐1 and type‐2 diabetic animals . The opioid μ‐receptor is primarily involved in the hypoglycaemic action of natural products in STZ‐diabetic rats . This finding was characterized using opioid μ‐receptor receptor knockout mice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Karam's study, too, FBS was lower in diabetic addicts, but it was not significant (20). Elevated glucose utilization and decrease of hepatic gluconeogenesis due to activation of peripheral opioid µ-receptors (MOR) and modification of glucose metabolismassociated genes have been proposed as the involved mechanisms in decreasing plasma glucose level (21). The effect of morphine on serum level of glucose has been demonstrated on animals (5,8,22,23).…”
Section: Discussionmentioning
confidence: 96%
“…Activation of these receptors might enhance the expression of muscle GLUT and/or reduce hepatic gluconeogenesis at the gene level [171] . MOR-induced glucose uptake is accomplished by increased gene expression of GLUT-4 via a phospholipase C-protein kinase (PLC-PKC) dependent pathway [172] . It has also been observed that stimulation of α1-adrenoceptors in the adrenal gland provokes the secretion of β-endorphin [173] depending also on the PLC-PKC pathway [174,175] .…”
Section: Roles Of Endogenous Opioids On Glucose Homeostasismentioning
confidence: 99%